Predictive Factors for the First Recurrence of Clostridioides difficile Infection in the Elderly from Western Romania - Iosif Marincu; Felix Bratosin; Iulia Vidican; Bianca Cerbu; Mirela Turaiche; Livius Tirnea; Madalina Timircan (Medicina, 2020)
Background and objectives: At present, Romania and parts of the European Union are facing an increasingly challenging public health problem consisting of nosocomial Clostridioides difficile infection (CDI), mostly in the elderly. Relapse cases have become more frequent, which present higher morbidity and mortality rates than the initial CDI infection. The aim of this study is to determine the predictive factors for recurrence, with the purpose of reducing the exposure of patients diagnosed with CDI, as well as aiming to initiate early treatment. Materials and Methods: In this retrospective descriptive study, we analyze a database from the First Department of Infectious Diseases at the Dr. Victor Babes Clinical Hospital for Infectious Diseases and Pulmonology in Timisoara, looking for patient history of CDI recurrences. We analyzed CDI recurrence in patients aged ≥65 years from 1 January 2016 to 31 December 2019, identifying 77 cases of CDI recurrence. The determination of predictive factors for recurrence involved the formation of a randomized control group, consisting of 74 patients aged ≥65 years who were diagnosed with C. difficile enterocolitis, but did not suffer a recurrence and survived ≥2 weeks after symptom onset. Results: Immunocompromised status, pre-existing gastrointestinal disease, and fever on initial hospitalization for CDI were all found to be significant independent positive predictive factors for the condition recurring in elderly Romanian patients. Conclusions: As the geriatric population in Romania grows, the national health system becomes increasingly overburdened, both from a financial standpoint and a human resources perspective. The analysis of factors predictive for CDI recurrence is, thus, of the utmost importance, particularly for the early identification of patients most at risk of CDI recurrence. Our findings could help physicians to identify recurrence early, consequently benefitting patients by a rapid intervention with a potential decrease in the associated complications and mortality.